Noncommutative complex GrosseWulkenhaar model - HOUNKONNOU, MAHOUTON NORBERT; OUSMANE SAMARY, DINE (My University, 2008)
This paper stands for an application of the noncommutative (NC) Noether theorem, given in our previous work [AIP Proc 956 (2007) 55-60], for the NC complex Grosse-Widkenhaar model. It provides with an extension of a recent work [Physics Letters B 653 (2007) 343-345], The local conservation of energy-momentum tensors (EMTs) is recovered using improvement procedures based on Moyal algebraic techniques. Broken dilatation symmetry is discussed. NC gauge currents are also explicitly computed.
Keywords: noncommutative field theory